(untitled) (Acta Scientiarum. Health Sciences, 2020)
This study aimed to develop and evaluate a prototype with opportunities for improvement for the e-SUS Primary Care module, integrated in the proprietary system used at the research site, with a view to improving the health information system. It is an applied research, with a qualitative approach, in the action-research modality. The population consisted of all (30) Community Health Agents assigned to six Family Health Centers in the city of Ribeirão Preto, State of São Paulo, Brazil and six computer experts, who agreed to participate in the research by signing the Informed Consent Form. The study was developed in three stages. Stage 1 - Knowledge brought by the Community Health Agent (CHA): observation, by the researcher, of the execution of professional activities in the Electronic Unified Health System of Primary Health Care and unstructured interview, between May and July 2016; Stage 2 - Construction of the prototype with opportunities for improvement for the e-SUS AB module. We used the AXURE RP Pro 7.0 software. Stage 3- Evaluation of the prototype by the CHA and computer experts. An evaluation instrument was developed considering the specifications described by ISO/IEC 25010, 9241 and 14598 with the parameters: poor, fair, good and excellent. The results show the importance of knowing the aspects related to the way of working, or behavior, that can influence the final quality of the data inserted in the Health Information Systems. In the same way, such systems aim to obtain inputs for the definition of the requirements and goals of usability, in order to meet the different user roles identified, and also reinforces the relevance of looking at own systems, acquired in the private market or developed in the municipality. The rapprochement between the researcher and the people involved in the investigated situation allowed for the detection of gaps between the indispensable components to carry out the actions that aim to consolidate computerization in health and, above all, to outline potential solutions to the problems identified.